KUALITAS PELAYANAN PEMBERIAN KREDIT TERHADAP PENINGKATAN KREDIT PEMILIKAN RUMAH (KPR) - Husnawaty, Husnawaty (STIEM BONGAYA, 2020)
The purpose of this study was to determine the impact of loan service quality on the increase in PT home ownership loans (KPR). Bank of Indonesia (Persero), Tbk Mattoangin Makassar branch. The analysis method used in this study is the multiple linear analysis method. The result of the study is PT. The Tbk Makassar Mattoangin sub-branch of the National Bank of Indonesia (Persero) should make improvements in the provision of credit services, especially in terms of reliability, in order to avoid customer complaints and strive to fulfill their hopes and wishes for customers. And it should maintain or even increase the mortgage to customers (KPR)